KEPUASAN LAYANAN KESEHATAN POLI UMUM DI RSIA ARAFAH ANWAR MEDIKA SUKODONO SIDOARJO - Nur Ilahi Anjani (UNUSA Press, 2018)
This study aims to determine the satisfaction of patients in using health services at general polyhospital of Arafah Anwar Medika Sukodono in Sidoarjo. The survey was conducted on 50 newpatients who received health services at Polia General Hospital Anwar Medika Sukodono SidoarjoRegency. Instruments are structured questionnaires through PSQ (Patient SatisfactionQuestionnaire). Data were analyzed using descriptive statistical test through the frequencydistribution table. Research shows the satisfaction of respondents to service in general poly in generaland the satisfaction of respondents related to facilities in the general poly is good. Satisfaction ofrespondent to physician ability and doctor's accuracy is good. Satisfaction of respondent to attitudeof doctor and nurse to patient have good. Satisfaction of respondent on giving information fromdoctor have good. Satisfaction of respondents related to the conformity of cost is good. Satisfactionof respondents at the time of examination is also good. And the satisfaction of respondents related tothe access of respondents is good. This research recommends follow-up related inputs, suggestions,complaints from the public related to the service so as to provide the best solution to the problemsfaced by customers and conduct regular and continuous surveys to maintain the quality of service.